1984
DOI: 10.1159/000179983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracerebroventricular Clonidine on Serum Corticosterone Levels in Rats

Abstract: In conscious, nonstressed rats clonidine given intracerebroventricularly (i.c.v.) increased the pituitary-adrenocortical response evaluated indirectly from corticosterone concentration. The maximum significant increase occurred 60 min after a dose of 10 µg. The α2-adrenoceptor antagonist yohimbine given alone i.c.v. in low doses (0.05–1 µg) had no effect on plasma corticosterone levels, but at higher doses (5 and 10 µg) it produced a significant rise in these levels. Phenoxybenzamine (0.05-10 µg, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…However, no clear conclusions can be found in the scanty literature on icv administration of catecholamines. It has been reported that icv injections of the « 2 -agonist clonidine lead to increased corticosterone release, and that the effect is reversed by the a 2 -blocker yohimbine, but not by the preferential «i-blocker phenoxybenzamine (23). These results were taken as favoring the theory that catecholamines inhibit ACTH release via presynaptic a 2 -receptors, in agreement with hypotheses based on findings in the dog (1, 2).…”
Section: Discussionsupporting
confidence: 88%
“…However, no clear conclusions can be found in the scanty literature on icv administration of catecholamines. It has been reported that icv injections of the « 2 -agonist clonidine lead to increased corticosterone release, and that the effect is reversed by the a 2 -blocker yohimbine, but not by the preferential «i-blocker phenoxybenzamine (23). These results were taken as favoring the theory that catecholamines inhibit ACTH release via presynaptic a 2 -receptors, in agreement with hypotheses based on findings in the dog (1, 2).…”
Section: Discussionsupporting
confidence: 88%
“…The injection of clonidine resulted in a significant stimulation of corticosterone secretion which agrees with the findings of others (37,(39)(40)(41). Previously we could not show any clonidine-mediated stimulation of corticosterone release, possibly because the basal corticosterone levels of the control rats were relatively increased as a result of suboptimal experimental conditions (18).…”
Section: Discussionsupporting
confidence: 92%
“…Current evidence strongly favours a stimulatory action for noradrenaline (12,13,35), although inhibitory effects have also been reported (36)(37)(38). Most of the discrepancies appear to result from differences in methodological approaches eg.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the facts that clonidine, another (x2-adrenoceptor agonist, increases both plasma glucagon (Gotoh et al 1988) and corticosterone (Zacny and Bugajski 1984) concentrations in rats. Since the secretion of catecholamines is negatively controlled by c~2-adrenoceptors (Sakurai et al 1983), they probably did not contribute to the hyperglycemia in our studies with amitraz.…”
Section: Discussionmentioning
confidence: 80%